Potential modulating effects of Allium mongolicum regel ethanol extract on rumen fermentation and biohydrogenation bacteria of dairy cows in vitro - Wang, XiaoYuan; Bai, Chen; Khas Erdene; Umair, Ashraf Muhammad; Cao, QiNa; Ao, ChangJin; Jiang, LinShu (Frontiers in Microbiology, 2023)
The objective of this study was to evaluate the potential modulating effects of Allium mongolicum regel ethanol extract (AME) on rumen fermentation and biohydrogenation (BH) bacteria in vitro. Four Holstein cows were used as donors for the rumen fluid used in this study. In experiment 1, five treatments (supplemented with 0 mg/g, 1 mg/g, 2 mg/g, 3 mg/g, and 4 mg/g of AME based on fermentation substrate, respectively) were conducted to evaluate the effects of different levels of AME on fermentation status in vitro. The results showed that after 24 h of fermentation, MCP was reduced with AME supplementation (p < 0.05), and the multiple combinations of different combinations index (MFAEI) value was the highest with 3 mg/g of AME. In experiment 2, six treatments were constructed which contained: control group (A1); the unsaturated fatty acid (UFA) mixture at 3% concentration (A2); the mixture of A2 and 3 mg/g of AME (A3); 3 mg/g of AME (A4); the UFA mixture at 1.5% concentration (A5); the mixture of A5 and 3 mg/g of AME (A6). The abundance of bacterial species involved in BH was measured to evaluate the potential modulating effect of AME on rumen BH in vitro. Compared with the A1 group, the A3, A4, and A6 groups both showed significant decreases in the abundance of rumen BH microbial flora including Butyrivibrio proteoclasticus, Butyrivibrio fibrisolvens, Ruminococcus albus and Clostridium aminophilum (p < 0.01). The A3 group was less inhibitory than A4 in the abundance of B. proteoclasticus, B. fibrisolvens, and R. albus, and the inhibitory effect of the A6 group was higher than that of A4. In conclusion, the supplementation with 3 mg/g of AME could modulate the rumen fermentation and affect BH key bacteria, which suggests that AME may have the potential to inhibit the rumen BH of dairy cows.